Adropin Alleviates Myocardial Fibrosis in Diabetic Cardiomyopathy Rats: A Preliminary Study - Liu, Mao; Ai, Jiao; Shuai, Zhuang; Tang, Kai; Li, Zongyu; Huang, Yin (Frontiers in Cardiovascular Medicine, 2021)
Aim: Adropin (ADR) is a novel regulatory polypeptide and has important effects on energy metabolism in the heart. However, it is still unclear whether ADR can relieve ventricular remodeling in DCM. Therefore, this study was conducted to assess the effect of ADR on myocardial fibrosis in DCM rats. Materials and Methods: Twenty Wistar rats were randomly assigned into four groups: healthy control group (CON), DCM model group (DCM), DCM model treated with ADR group (ADR) and DCM model treated with perindopril group (PER). Collagen volume fraction (CVF) and perivascular collagen area (PVCA) were calculated. Diastolic function was assessed by echocardiography. The mitochondrial membrane potential assay was conducted by Rhodamine 123 staining. The protein expression levels of Col I, Col III, Mitofusin-1, Mitofusin-2 and Drp1 were evaluated using western blot. Results: Compared to CON group, CVF, PVCA and the relative protein expression of Col I, Col III and Drp1 increased in DCM group. And the relative expression of Mitofusin-1 and Mitofusin-2 proteins decreased. During our investigations, CVF, PVCA and the relative protein expression of Col I, Col III and Drp1 decreased in ADR treated rats compared to DCM group. The diastolic function was elevated in ADR group. The fluorescence of Rhodamine 123 and the expression of Mitofusin-1 and Mitofusin-2 also increased in ADR group. Conclusion: Our study demonstrated that ADR could alleviate myocardial fibrosis and improve diastolic function in DCM rats. ADR may be a putative candidate for the treatment of DCM.